Influence of Work Experience, Integrity, Objectivity and Competence Toward Audit Quality at Public Accounting Firm in Surabaya - Shiera Sagita; Senny Harindahyani (Perpustakaan Universitas Surabaya, 2020)
Abstract–The purpose of this research is to analyze the influence of work experience, integrity, objectivity, and competence toward audit quality at public accounting firm in surabaya. The object of this study is independent auditor that working at public accounting firm in surabaya with the position from junior level to senior level. The primary data that processed is data from questionnaire that has been distributed to 60 auditor as respondent. This study use data from 2017 and the questionnaire is distributed in 2018. The result of this study shows that work experience and integrity has significant influence and positive correlation toward audit quality. On the contrary, objectivity has not significant influence but positive correlation toward audit quality. Then, competence has not significant influence and negative correlation toward audit quality.Keywords: audit quality, work experience, integrity, objectivity, competence